Pengelolaan Badan Usaha Milik Desa Untuk Meningkatkan Perekonomian Dan Kesejahtraan Masyrakat Desa Pinang Merah Kecamatan Pamenang Barat Kabupaten Merangin - Dewi untari; As’ad Isma; Faturahman Faturahman (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to analyze BUMDes management in improving community welfare. The data collection methods used were observation methods, interview methods and documentation methods. The research method uses qualitative research, namely research aimed at describing and analyzing phenomena, events. The object used is the people of Pinang Merah Village. The research results show that BUMDes Sumber Jaya is a facility or business unit that can help the community increase their income. The role of BUMDes Sumber Jaya in helping overcome the community's economic problems is sufficient, although not optimal. Several business units run by BUMDes Sumber Jaya are running well, as can be seen from the convenience of the community. Although there is one type of business that is not running, namely tourism management.